The Morphological and Anatomical Studies of The Aerial Parts of Abroma augusta L. from Semarang - Rita Ariyana Nur Khasanah; Niken Kusumarini (Jurnal Biodjati, 2021)
Abroma augusta L. known as Devil’s cotton belongs to Malvaceae. The exploratory study aimed to study the morphological and anatomical characteristics of the aerial parts of A. augusta L. from Semarang. The transverse section of the aerial parts was made by a simple method (fresh preparation) and then observed under a binocular microscope with an optilab. All characteristics were observed and then compared with the references. The collected data were analyzed descriptively and quantitatively. In summary, the results showed that A. augusta L. was an evergreen shrub (small tree) with orthotropic and plagiotropic branches and polymorphous leaves. The inflorenscence was found in the terminal and axillar plagiotropic branching with bisex, actinomorphic, and pentamerous flowers. The fruit was unique (obconical capsule with a rounded base and truncate-tip with 5 angled wings) including cotton fibers and numerous black seeds. The petiole was composed of epidermis, collenchyma, cortical parenchyma, sclerenchyma, vascular bundle, mucilaginous ducts, and pith. The dorsiventral leaf was composed of upper and lower epidermis, palisade, and spongy parenchyma. The stomata type was ranunculaceous (anomocytic) while the guard cell was kidney-shaped. The stomata density on the abaxial leaf was higher than that of the adaxial leaf. The stellate and unicellular non-glandular trichomes, and capitate glandular trichomes were found abundantly on the petiole and leaf blade. These morphological and anatomical studies are important to support the identification as a part of the conservation effort of the plant. Further studies are recommended to investigate the root morphology and anatomy and also biochemical characteristics of each part of the plant in order to obtain  complete plant identification.